Expert and novice soccer goalkeepers` visual perception: a practical-coaching approach eye-tracking - Piechota, K.; Borysiuk, Z.; Zmarzly, D.; Jonek, M.; Majorczyk, E. (International Journal of Performance Analysis in Sport, 2025)
One of the most important determinants of effectiveness in sports is a high level of visual perception as a leading decision-making factor. Two groups of soccer goalkeepers of 30 people each (A - seniors, 22.5 ± 2.25 years; B - novices, 15.40 ± 1.22 years) were studied. Eye-tracking glasses (Tobii Glasses 2) were used for the study. Three attempts were made to take a shot on goal in a fragment of a two-on-one play, after a pass and after a centring. Experienced (A) focused their gaze - after the pass - mainly on the ball, and in the next phase mainly on the striking foot. Novices (B) mostly directed their gaze first to the ball and foot, and in the last phase also to knee, shin and ground. Experienced (A) showed a longer fixation of their gaze on the attacker (taking a shot on goal) - (197.62 ms), compared to novices (B) (183.20 ms). The results of the study indicate that experienced goalkeepers show greater focus, composure on the object and better decision-making. Goalkeepers` decision-making time is a factor that is important and constantly in need of researchers` attention in order to achieve better sports performance. Therefore, similar studies should continue.